Desert queen - Gopal, Jyoti Rajan (Levine Querido, 2023)
"As a young boy, Harish hears and feels the music of the Thar Desert, all around him: "When the khamaicha thrums and the dholak drums and the boy's feet tap and his fingers sway... it is softly... softly, so no one sees." Harish knows the line between what men and women should want, and he keeps it in sight. But when Harish's family suffers loss, he finds himself in charge of two sisters, in charge of making money. And so he begins to dance publicly, in the bright colors and kohl rimmed eyes of the god Krishna.. and in the rhythm-making anklets and the swirling costumes of the female Rajasthani dancers he so admired. A new persona is born. The path of Queen Harish to stardom is not without trial, but it is one of bravery and fearlessness. A story of triumph and inspiration. Something to sing about out loudly, proudly, so everyone can hear." --